PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH DI KAUPATEN BENGKALIS TAHUN 2014 - Pika Julianti; Dodi Haryono; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
This study entitled "Public Participation in Formation of Regional Regulation inBengkalis 2014." author's interest to do this research is that the author encounteredproblems that occur in Bengkalis, ie people who have never been involved eitherdirectly or indirectly in the process of lawmaking area. It is clearly not in accordancewith Article 96 of Law No. 12 of 2011 Concerning the Establishment RegulationLegislation, which states that "The public has the right to provide input orally and / orin writing referred to can be made through a public hearing, the working visit ,socialization and / or, seminar, workshops and / or discussion. "This study aims to determine the level of public participation in theestablishment of Regional Regulation in Bengkalis 2014, to determine the constraintsaffecting public participation in the establishment of local regulations in Bengkalis2014 and to identify efforts to be made so that these obstacles can be overcome so thatthe people of Bengkalis can be a participatory community. In order to achieve the goalsthat the authors wish, the author conducted research with sociological method, which isreviewing the existing situation in the field and then linked with the prevailinglegislation is done on location study using data collection tools ie by way of aninterview with the parties concerned , such as, Member of Provincial ParliamentBengkalis district, Bengkalis District Legal Secretariat and some societies in theBengkalis District. Meanwhile, judging from its nature, this research is descriptive, theresearch illustrates clearly and in detail and explain the realities in the field ofcommunity participation in the formation of local regulations in Bengkalis 2014.In this study the authors used data collection techniques such as interviews,questionnaires and literature study. Based on the problem formulation and discussionof the issues, the data analysis used by the author is by way of qualitative, that outlinesthe data generated in the form of a regular sentence, logically and effectively so as toprovide an explanation for the formulation of the author adopted. While the method ofthinking yangpenulis use in drawing conclusions is the deductive method. Deductivemethod is a way of thinking that draw a conclusion on matters of a general naturebecomes a declaration of a special nature. This can assist authors in conductingresearch on public participation in the establishment of local regulations in Bengkalis2014.Keywords: Public Participation, Local Regulation, Bengkalis.